(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2023)
Question: What is the distribution of Viola sororia in Ukraine? Locations: Cherkasy, Kyiv, Poltava, Sumy, Zakarpattia & Zhytomyr Regions. Methods: field research and critical analysis of herbarium collections of the M.G. Kholodny Institute of Botany of the National Academy of Sciences of Ukraine (KW) and the M.M. Gryshko National Botanical Garden of the National Academy of Sciences of Ukraine (KWHA), data from the literature and the iNaturalist electronic resource. Nomenclature: Galasso et al. 2018, Marcussen et al. 2022, POWO 2023. Results: The generalized data about current distribution of Viola sororia (Violaceae), a new alien species of Ukrainian flora was reported. Species is wide cultivated in Ukraine in many botanical gardens, arboretums, urban parks and private gardens. The species was recorded in several localities in the country as escaped plant as well as on the territories of cultivation and outside them (spontaneous distribution). The taxonomical position and the main morphological characteristics, chorological data (primary and secondary ranges), ecological and coenotic peculiarities were given. The species has North American origin. In Ukraine, it considers as ergasiophygophyte and colonophyte according to degree of naturalization. Mainly plants occurs as single or in small groups in unformed plant communities. The species show a tendency to penetration in natural forest coenoses in Zhytomyr Polissia. The map of distribution of Viola sororia in Ukraine in culture and spontaneous localities was presented. Conclusions: The spontaneous distribution of Viola sororia has been recorded in the Carpathians Mts, mixed forests zone and forest-steppe zone. In total, 21 locations of the species were noted outside the cultivated areas in six administrative regions of Ukraine, in large cities and their surroundings. Among them, 7 localities were found from scientific centers of plant introduction.